Trust in crisis: Conspiracy mentality, lack of trust and religiosity predicted conspiracy beliefs about COVID-19 in a Norwegian sample - Dyrendal, Asbjørn (Approaching religion, 2021)
Crises are associated with a search for meaning and security. In recent years, they have also been associated with increased attention to conspiracy theories. Such theories about COVID-19 have been many. We have looked at several COVID-specific conspiracy theories and their relation to a number of other factors, including religiosity in a highly educated Norwegian convenience sample (n=1225). Conspiracy mentality, lack of trust, and religiosity were directly associated with conspiracy beliefs about COVID-19, whereas self-reported stress and negative emotions related to the pandemic had only small, indirect effects. Unlike previous research findings, we found no effect of gender or age.